PEMBELAJARAN MOTORIK KASAR MELALUI PERMAINAN SIRKUIT WARNA - sofia, ari; fatmawati, nia (FKIP Universitas Lampung, 2016)
Gross Motoric Learning Through Colour Circuit. The availability of game is being the main asset in early childhood activities. This research was motivated by the colour circuit game conducted by the early childhood teachers which has not been developed. The purpose of this qualitative study was to observe how the steps in developing the color circuit game and how design of educative game tools in colour circuit game. The method used was research and development of colour circuit game with the research subjects were the students of group B in TK Negeri Pembina Metro Timur. The result of the developments are the activity of colour circuit. The results of this research showed that the colour circuit game is 94 % easy to be done by children, 100 % safe and 100 % fun for children Keywords: learning , gross motor, colour circuit DOI: http://dx.doi.org/10.23960/jpp.v6.i1.201601